2020
DOI: 10.1021/acsomega.0c02679
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of NiFeCo Trinary Oxy-Hydroxides for an Efficient and Stable Oxygen Evolution Reaction Catalyst

Abstract: NiOOH and its doped species are widely used as electrocatalysts for the oxygen evolution reaction (OER) in alkaline media. In this work, we carried out comprehensive density functional theory (DFT) simulations of Ni-based electrocatalysts for the OER by applying suitable dopants in β-NiOOH. A range of Fe and Co atoms (%) are employed as doping agents to increase the overall catalytic ability, stability, and feasibility of NiOOH. Our simulations indicate that Ni 88% Fe 6% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…[10] A recent density functional theory study of NiFeCo (oxy)hydroxides showed that mild doping with cobalt into NiFe increased the surface formation and water adsorption energy, leading to the improved preliminary OER stability and activity of the catalyst. [32] Even though the catalysts synthesized in the presence of a larger amount of cobalt nitrate, i.e., 4/8/16 and 32 mM, revealed much higher active surfaces, their OER performance decreased with the higher cobalt nitrate concentration. This may be related to the formation of the less stable catalyst (Figure 1a), the presence of the catalyst's agglomerations and cracks (Figure 2), precipitation of the additional cobalt phase (Figure 3a,b), or fewer amount of Co, Ni, Fe species at the third oxidation state (Figure 3 and 4).…”
Section: Discussionmentioning
confidence: 97%
“…[10] A recent density functional theory study of NiFeCo (oxy)hydroxides showed that mild doping with cobalt into NiFe increased the surface formation and water adsorption energy, leading to the improved preliminary OER stability and activity of the catalyst. [32] Even though the catalysts synthesized in the presence of a larger amount of cobalt nitrate, i.e., 4/8/16 and 32 mM, revealed much higher active surfaces, their OER performance decreased with the higher cobalt nitrate concentration. This may be related to the formation of the less stable catalyst (Figure 1a), the presence of the catalyst's agglomerations and cracks (Figure 2), precipitation of the additional cobalt phase (Figure 3a,b), or fewer amount of Co, Ni, Fe species at the third oxidation state (Figure 3 and 4).…”
Section: Discussionmentioning
confidence: 97%
“…Hydrogen energy is considered as an ideal green energy source, and the product of hydrogen combustion is H 2 O, so hydrogen, when used as fuel, it both solves the future fossil fuel crisis and shortage and lessens the environmental pollution from fossil fuel consumption [150,210,[213][214][215]. In 1972, Fujishima et al first described the TiO 2 photoelectrode water splitting phenomenon [216], and as a result, photocatalytic H 2 production has gained much attention [217][218][219][220].…”
Section: Water Splittingmentioning
confidence: 99%
“…Using density functional theory (DFT), spectroscopic methods and docking to deduce the structural activity of a drug could open the path for the creation of novel antibacterial inhibitors. Despite the fact that DFT studies on pyridine derivatives have been reported, no spectral study or DFT studies on doxylamine succinate (DXS) have been conducted [18][19][20].The use of quantum chemical computations supported by DFT in vibrational spectral analysis of DXS is an efficient way for analyzing the many forms of bonding and normal modes of vibration [21,22]. Potential energy distributions have been used to support the entire vibrational assignments for all vibrational modes.…”
Section: Introductionmentioning
confidence: 99%